Defining intra-tumoral and systemic immune biomarkers for locally advanced head-and-neck cancer – detailed protocol of a prospective, observatory multicenter trial (ImmunBioKHT) and first results of the immunophenotyping of the patients’ peripheral blood - Donaubauer, Anna-Jasmina; Frey, Benjamin; Weber, Manuel; Allner, Moritz; Vogl, Christoph; Almajali, Omar; Kuczera, Lukas; Tamse, Henriette; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Zülch, Lilli; et al. (Frontiers in Oncology, 2024)
The approval and effectiveness of immune checkpoint inhibitors in head-and-neck squamous cell carcinoma (HNSCC) highlights the role of the immune system in this tumor entity. HNSCCs not only interacts with the immune system in the tumor tissue, but also induce systemic effects that may be additionally influenced by further factors such as the microbiome. Nonetheless, reliable immunological biomarkers that predict treatment response and outcome in HNSCC patients are lacking. The currently available biomarkers are mainly limited to analyses from tumor biopsies, while biomarkers from liquid biopsies, such as peripheral blood are not well-established. Thus, the here presented trial aims to identify interactions of intra-tumoral and systemic immune responses and to define prognostic immune signatures. Consequently, not only samples from the tumor tissue, but also from peripheral blood and the microbiome will be studied/are being evaluated and correlated with the clinical outcome. In this prospective, multi-center trial, 1000 HNSCC patients and 100 patients in the control cohort with non-tumor head-and-neck surgery will be enrolled. The local immune status from of the tumor and the microbiome will be sampled before treatment. In addition, the systemic immune status from peripheral blood will be analyzed before and after surgery and after the adjuvant and definitive radio-chemotherapy (RCT). Clinical baseline characteristics and outcome will additionally be collected. Data mining and modelling approaches will finally be applied to identify interactions of local and systemic immune parameters and to define prognostic immune signatures based on the evaluated immune markers. Approval from the institutional review board of the Friedrich-Alexander-Universität Erlangen-Nürnberg was granted in December 2021 (application number 21-440-B). By now, 150 patients have been enrolled in the intervention cohort. The results will be disseminated to the scientific audience and the general public via presentations at conferences and publication in peer-reviewed journal
CRIS-Team Scopus Importer:2024-10-04
Keywords: HNSCC; immune monitoring; immunological biomarker; liquid biopsy; prospective clinical trial

Perioperative anticoagulation in free microvascular flaps – a comparison of different prophylactic regimes in oncologic reconstructive surgery - Tamse, Henriette; Koch, Michael; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Balk, Matthias; Rupp, Robin; Allner, Moritz; Iro, Heinrich; Sievert, Matti (European Review for Medical and Pharmacological Sciences, 2024)
OBJECTIVE: Free tissue transfer has an established place in oncologic head and neck surgery. However, the necessity and specific regimen of perioperative thromboprophylaxis remain controversial. Here, the risk of postoperative hemorrhage contrasts with vascular pedicle thrombosis and graft loss. This work compares three different heparin protocols (AC) with regard to postoperative complications. PATIENTS AND METHODS: A retrospective analysis of our free flap transplants between 2004 and 2023 was conducted. Inclusion criteria were thromboprophylaxis with (A) 500 IU/h unfractionated heparin (UFH), (B) low-molecular-weight heparin (LMWH) once daily, and (C) LMWH once daily with additional immediate preoperative administration. Primary endpoints were the incidence of postoperative bleeding and hematoma and the appearance of flap thrombosis. RESULTS: We evaluated 355 cases, 87 in group A, 179 in group B, and in group C 89 patients. Overall, postoperative bleeding occurred in 8.7% of patients, and 83% underwent hemostasis under intubation anesthesia, with no significant difference between groups (p = 0.784). Hematoma formation requiring revision was found in 3.7% of patients (p = 0.660). We identified postoperative hematoma as a significant influencing factor for venous pedicle thrombosis (OR 3.602; p = 0.001). Venous and arterial flap thrombosis in the graft vessel showed no difference between the groups (p = 0.745 and p = 0.128). CONCLUSIONS: The three anticoagulation regimens appear to be equivalent therapy for the prevention of thrombosis without significant differences in postoperative bleeding. The use of LMWH with additional preoperative administration can, therefore, be administered in free flap reconstruction.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Anticoagulation; Bleeding; Flap thrombosis; Free flap; Hematoma; Heparin; Microvascular reconstruction